Аналіз можливості застосування технології blockchain у сфері управління ланцюгами постачань - Шльончак, І. А.; Солтус, А. П.; Рудь, М. П.; Shlionchak, I.; Soltus, А.; Rud, M. (ЦНТУ, 2023)
В статті виконано детальний аналіз вітчизняного та закордонного досвіду використання технології blockchain. Показано позитивний досвід такого використання. Акцентовано увагу на перевагах і недоліках даної технології. Проведено моніторинг доходів відомих світових компаній, що застосовують зазначену технологію. Підкреслено можливість ефективного використання blockchain-технології в сфері управління ланцюгами постачань в українській перспективі, особливо беручи до уваги європейський вектор розвитку країни. Human life in today's world is increasingly becoming faster and more popular in the digital format. Such a trend is observed in almost any sphere of human activity. And supply chain management is no exception. It is in the field of supply chain management that a digital approach to solving various problems is an extremely urgent task facing scientists today. The article provides a detailed analysis of the domestic and foreign experience of using blockchain technology. Positive experience of such use is shown. Attention is focused on the advantages and disadvantages of this technology. Monitoring of revenues of well-known global companies using the specified technology was carried out. The possibility of effective use of blockchain technology in the field of supply chain management in the Ukrainian perspective is emphasized, especially taking into account the European vector of the country's development. One of the European countries, namely Estonia, can be cited as an example of the effective use of blockchain technologies. One of the reasons for this is state support for digital technologies. The Estonian project is the most successful of the world's digital projects. Summing up, it should be noted that the application of blockchain technology has great prospects for effective use in the digital sphere of any human activity, in particular, in the management of supply chains. In the work, the main advantages and disadvantages of the mentioned technology were highlighted in order to establish greater efficiency of its application in the field of supply chain management. Based on the above, it should be concluded that blockchain digital technology is a promising system in the Ukrainian vector of European integration.
Analysis of the Possibility of Applying Blockchain Technology in the Field of Supply Chain Management
Keywords: управління ланцюгом постачань; ланцюг постачань; технології управління; цифровий формат; трансакції; supply chain management; supply chain; management technologies; digital format; transactions